Model Pembelajaran Pendidikan Agama Islam Berbasis Proyek Kesadaran Lingkungan Di Sekolah - Fitriani Ulayya, Aqila; Wahab, Wahab; Kurniawan, Syamsul (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2025)
The writing of this article is based on the lack of environmental awareness of students at school. Therefore, the purpose of writing this article is to find out how the project-based Islamic Religious Education learning strategy for environmental awareness at school, besides that it is hoped that students can have environmental awareness at school by not throwing garbage in any place, being able to sort garbage properly and processing waste by utilizing existing school resources through interesting Islamic Religious Education lessons. The writing of this article uses qualitative research methods by using a literature study approach (Liberary research) to analyze the learning strategy of Islamic religious education based on environmental awareness projects. The conclusion of this research in general is that this strategy is carried out with project activities made by the students themselves with the following steps: 1) Research or search for problems about the cleanliness of the school environment; 2) then afterwards conduct an environmental campaign using posters not to throw garbage in place which are prepared at the next meeting; 3) Practical learning to select and categorize organic and inorganic waste; and 4) Recycling waste by trying to make ecobricks from used plastic bottles and plastic waste.